Forbidden X-ray diffraction of highly B doped diamond substrate. (24th June 2021) - Kouda, K.; Sato, Y.; Takeuchi, M.; Takahashi, H.; Shikata, S.
Abstract: The (222) forbidden diffraction of a highly B doped high-pressure high-temperature (HPHT) diamond crystal was investigated by precise mapping using synchrotron radiation X-ray diffraction. The intensity ratios of (222) to (111) were high, ranging from 20% to 36% for the high-density dislocation areas with stacking faults (SFs), whereas the intensity ratios for the low-density dislocation areas ranged from 11% to 20%. For the high-density dislocation areas, the intensity distribution was very high in the upper region, which might correspond to the dislocation density along the X-ray path. In contrast, the intensity ratio of high-quality undoped HPHT crystals ranged from 3.0% to 4.3%, which might be due to multiple reflections of the high-quality crystal. The substrate quality can be conveniently investigated prior to device fabrication by examining the intensity of the forbidden diffraction using laboratory X-ray diffraction equipment.